Quantum spin Hall phase in 2D trigonal lattice - Z. F. Wang (Nature Portfolio, 2016)
Whilst different models describing the two-dimensional quantum spin Hall effect exist, very few experimental systems have been realized in which to test theory. Here, the authors present a discrete trigonal lattice model for the quantum spin Hall effect and predict its realization in Au/GaAs(111).